2019
DOI: 10.21873/invivo.11482
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Haemostatic Dressing Prototypes for the Emergency Services in the Porcine Haemostatic System

Abstract: Background/Aim: Coagulopathy can develop when hemostatic dressings are used to stop massive bleeding, even in patients without prior history of clotting disorders. The selection of procoagulants, which effectively control bleeding and prevent disseminated intravascular coagulation (DIC) and thrombosis, is a significant challenge. The aim of this study was to evaluate the effect of two prototypes of haemostatic dressing in the porcine haemostatic system. Materials and Methods: The total number of animals used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(13 reference statements)
0
1
0
Order By: Relevance
“…Chitosan-based hemostatic dressings were also effectively used in rats [5,7] . The application of hemostatic dressings in pigs was more extensively researched [8][9][10] . Kozen et al [4] reported that Celox Gauze was as effective as two other hemostatic dressings, and it significantly improved survival rates in comparison with standard dressings.…”
Section: Letter To the Editormentioning
confidence: 99%
“…Chitosan-based hemostatic dressings were also effectively used in rats [5,7] . The application of hemostatic dressings in pigs was more extensively researched [8][9][10] . Kozen et al [4] reported that Celox Gauze was as effective as two other hemostatic dressings, and it significantly improved survival rates in comparison with standard dressings.…”
Section: Letter To the Editormentioning
confidence: 99%